The Palgrave Handbook of Global Digital Journalism
XXI, 444 p. 31 illus., 15 illus. in color.
Keywords: This book responds to mounting calls to broaden the theorization of digital journalism, addressing critical questions about an emerging yet rapidly expanding area of study, and presenting multiple entry points and approaches that help us understand digital journalism better. Seeking to establish itself as a rich resource and a defining reference point for the evolving field, the handbook provides a critical appraisal and a useful overview of novel approaches and concepts, backed by a full breadth of dynamic and diverse interactions drawn from overlapping and critical studies by some of the leading experts on digital journalism. This handbook presents multiple methodological perspectives, reporting strategies, threats and opportunities and valuable insights on future trajectories for digital journalism practice in an era dominated by digital media technology. Split into four parts, it has been uniquely assembled to investigate and critique the full potential of digital journalism capturing broader, cross-cultural perspectives from all four corners of the world. Bruce Mutsvairo is Professor in the Department of Media and Culture Studies at Utrecht University, Netherlands, where he doubles as the UNESCO Chair on Data, Disinformation and Democracy. Kristin Skare Oregeret is Professor of Journalism at Oslo Met University, Norway.